Polymer–metal–organic framework self-assembly (PMOFSA) as a robust one-step method to generate well-dispersed hybrid nanoparticles in water. Issue 33 (3rd April 2023) - Li, Kun; Yu, Zhihao; Dovgaliuk, Iurii; Le Coeur, Clémence; Lütz-Bueno, Viviane; Leroy, Eric; Brissault, Blandine; de Rancourt de Mimerand, Yoann; Lepoitevin, Mathilde; Serre, Christian; Penelle, Jacques; Couturaud, Benoit
Abstract : A new process, PMOFSA, is described here, that opens the way for the one-pot straightforward and versatile manufacture of polymer-MOF nanoparticles in water. Abstract : A new process, PMOFSA, is described here, that opens the way for the one-pot straightforward and versatile manufacture of polymer-MOF nanoparticles in water. It can be expected that this study will not only expand the scope of in situ preparation of polymer-MOF nano-objects but also inspire researchers in the field to prepare a new generation of polymer-MOF hybrid materials.